2020
DOI: 10.5038/2640-6489.5.2.1130
|View full text |Cite
|
Sign up to set email alerts
|

Does employee envy trigger the positive outcomes at workplace? A study of upward social comparison, envy and employee performance

Abstract: The purpose of this research was to investigate the outcomes of envy in the workplace and the moderating role of perceived organizational support. Data was collected from 270 employees of the telecom industry. The cross-sectional research was conducted, and the data was collected through survey questionnaires from employees hailing from private Telecom companies in Pakistan. Results showed that upward social comparison initiates benign and malicious envy which, in turn, affects employee performance. Benign env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The results show that employees who are aware of the use of robots at work will be motivated to accept robots as colleagues; thus, they will consider robots as coworkers at work, which will reduce various psychological depressions and anxieties. In this case, management can support, develop and motivate employees (Khan and Noor, 2020). Recent studies have found that customers and employees perceive the use of robots differently but are self-motivated to use robots (Berezina et al , 2019; Liao and Sundar, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that employees who are aware of the use of robots at work will be motivated to accept robots as colleagues; thus, they will consider robots as coworkers at work, which will reduce various psychological depressions and anxieties. In this case, management can support, develop and motivate employees (Khan and Noor, 2020). Recent studies have found that customers and employees perceive the use of robots differently but are self-motivated to use robots (Berezina et al , 2019; Liao and Sundar, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With this study, we argue that envy can have a significant impact on employees' job performance. In the literature, some of the studies on workplace envy and job performance relation were conducted within the frame of typological approach (De Clercq et al , 2018; Aydın-Küçük and Taştan, 2019; Lee and Duffy, 2019; Khan and Noor, 2020; Zhang et al , 2020) mostly indicating malicious envy related to poor performance whereas benign envy to improvement in performance. Although there also exists a recent interest in the situational approach, a limited number of studies are available in the literature (Eissa and Wyland, 2016; Lee et al , 2018; Treadway et al , 2019; Shousha, 2020; Tariq et al , 2019) that show how envying others and being envied can contribute to employees' job performance.…”
Section: Discussionmentioning
confidence: 99%
“…Envy can motivate the “achieving of a standard of excellence” (Lange and Crusius, 2015: 289). An undercurrent of perhaps lesser-known studies of envy, such as that by Khan and Noor (2020: 182), consider that envy can “produce positive results.”…”
Section: Envy In the Westmentioning
confidence: 99%